Randomized trial finds that prostate cancer genetic risk score feedback targets prostate‐specific antigen screening among at‐risk men. Issue 22 (19th July 2016) - Turner, Aubrey R.; Lane, Brian R.; Rogers, Dan; Lipkus, Isaac; Weaver, Kathryn; Danhauer, Suzanne C.; Zhang, Zheng; Hsu, Fang‐Chi; Noyes, Sabrina L.; Adams, Tamara; Toriello, Helga; Monroe, Thomas; et al.
Abstract : BACKGROUND: Prostate‐specific antigen (PSA) screening may reduce death due to prostate cancer but leads to the overdiagnosis of many cases of indolent cancer. Targeted use of PSA screening may reduce overdiagnosis. Multimarker genomic testing shows promise for risk assessment and could be used to target PSA screening. METHODS: To test whether counseling based on the family history (FH) and counseling based on a genetic risk score (GRS) plus FH would differentially affect subsequent PSA screening at 3 months (primary outcome), a randomized trial of FH versus GRS plus FH was conducted with 700 whites aged 40 to 49 years without prior PSA screening. Secondary outcomes included anxiety, recall, physician discussion at 3 months, and PSA screening at 3 years. Pictographs versus numeric presentations of genetic risk were also evaluated. RESULTS: At 3 months, no significant differences were observed in the rates of PSA screening between the FH arm (2.1%) and the GRS‐FH arm (4.5% with GRS‐FH vs. 2.1% with FH: χ 2 = 3.13, P = .077); however, PSA screening rates at 3 months significantly increased with given risk in the GRS‐FH arm ( P = .013). Similar results were observed for discussions with physicians at 3 months and PSA screening at 3 years. Average anxiety levels decreased after the individual cancer risk was provided ( P = .0007), with no differences between groups. Visual presentation by pictographs did not significantly alter comprehension or anxiety. CONCLUSIONS: This is likely the first randomized trial of multimarker genomic testing to report genomic targeting of cancer screening. This study found little evidence of concern about excess anxiety or overuse/underuse of PSA screening when multimarker genetic risks were provided to patients. Cancer 2016;122:3564–3575 . © 2016 American Cancer Society Abstract : This prospective trial shows that the provision of individual genetic risk scores for prostate cancer does not lead to significant increases in anxiety or in the use of prostate‐specific antigen screening. Instead, genetic risk scores lead to the targeted use of prostate‐specific antigen screening among higher risk men, and this may improve prostate‐specific antigen screening performance.